2020
DOI: 10.1155/2020/2781350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IFN-Free and IFN-Based Treatment on Blood Myeloid Dendritic Cell, Monocyte, Slan-DC, and Activated T Lymphocyte Dynamics during HCV Infection

Abstract: Chronic hepatitis C virus infection leads to the activation of innate immunity, a key component in HCV fibrosis. In the past, the use of IFN-based treatment regimens did not permit an adequate evaluation of the impact of HCV clearance on immune cells, because of their antiviral and immunomodulatory properties. The recent development of direct-acting antiviral (DAA) therapy, which is associated with high rates of sustained virological response, enables a more accurate analysis of the immunological modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Previous studies on the effects of HCV used fresh or cryopreserved peripheral blood mononuclear cells (PBMCs) or monocyte-derived DCs (moDCs) and a limited number of phenotypic markers [17][18][19][20][21][22][23][24][25]. Isolation, cryopreservation and differentiation alter the phenotype and function of PBMCs and moDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of HCV used fresh or cryopreserved peripheral blood mononuclear cells (PBMCs) or monocyte-derived DCs (moDCs) and a limited number of phenotypic markers [17][18][19][20][21][22][23][24][25]. Isolation, cryopreservation and differentiation alter the phenotype and function of PBMCs and moDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The immunological response after eradication of HCV using IFN-free DAA therapies is not well defined. Several studies suggest a partial immunological recovery after treatment [ 42 , 43 , 44 ]. In our study, we found a different immune profile in the two populations in the monocyte and lymphocyte compartments as well as in levels of soluble markers after DAA treatment.…”
Section: Discussionmentioning
confidence: 99%